Roundtable on Mark A. Lause's Free Labor: The Civil War and the Making of an American Working Class. Issue 4 (5th December 2016) - Case, Theresa; Pearson, Chad; Kelly, Brian; Lause, Mark A.
Abstract : Mark A. Lause's Free Labor: The Civil War and the Making of an American Working Class is the most comprehensive book about the Civil War era labor movement published in more than a half century. While most scholars of the Civil War focus principally on the great battles, the political tensions between the North and South, and Abraham Lincoln's steady leadership, Lause has produced a thorough account of different laborers during wartime: solders, printers, molders, machinists, and, significantly, former slaves while never losing sight of the period's most remarkable military and political struggles. Built on various collections of primary sources and the most relevant secondary literature, the book will give future generations of historians much to contemplate. Recognizing the significance of Lause's scholarly contribution, three historians of labor have offered their thoughts. Theresa Case, author of an influential book about the great 1880s Southwest Railway strikes, provides a largely favorable review, applauding Lause for his close attention to cases of both repression and resistance, including outbreaks of interracial unity between blacks and whites. She challenges him for failing to highlight distinctions between freedom and slavery, but concludes by recognizing his "high standard of research." Chad Pearson, a scholar of union‐busting employers' associations, focuses on the contested meanings of the Civil War, Lincoln's leadership, and the notion of free labor itself. Pearson finds it noteworthy that both union activists in the 1860s and strikebreaking architects in the Progressive Era interpreted the war's meaning in starkly different ways. Brian Kelly, a leading historian of race and labor, questions why Lause was not more attentive to the role that nativism played in de‐radicalizing sections of the working‐class. Yet Kelly remains tremendously impressed, noting that Lause has demonstrated "encyclopedic knowledge of the [period's] labor and reform currents." Lause concludes the roundtable with his responses to all three contributors.